Factors Influencing the Purchase Decision of Retail Outlets in Coimbatore - A. Karthikeyan; Dr. M. Sadhika Sultana (International Journal of Engineering and Management Research, 2022)
Retail sector and Traditional marketplaces are giving way to new formats such as department stores, hypermarkets, supermarkets, and specialty stores as India's retail sector undergoes a massive transformation. Western-style malls have begun to pop up in metros and other locations, offering Indian shoppers a never-before-seen shopping experience. The sector is at a crossroads, with organized retailing and Indian population consumption both on a higher growth trajectory. The demographics of the Indian people are changing dramatically. Various factors such as the availability of professional practices, media proliferation, various brands that are gaining value and thus enhancing industry growth, the availability of various funding options, regulations such as VAT implementation to make processes simple, a sea change in the country's demographics, and international exposure all contribute to the industry's growth. The present study is an attempt to assess the factors influencing the purchase decision of retail outlets in Coimbatore.